Data Transmission Analysis using MW-5000 at 5.8 GHz Frequency - Abu Bakar Ibrahim; Ashardi Abas (Institute of Advanced Engineering and Science, 2018)
In the recent years, the data communication system become the main type of communication in the world. The FSK modulator or demodulator is one of the part that becomes the most important part and extremely advanced with the involvement of microwave active and passive circuits. This paper presents the data transmission analysis using MW-5000 at 5.8 GHz frequency. This experiment use the microwave communication module MW-5000 that is available in electronic laboratory. From this experiment the duration taken for the transmission of data is depend on the length of sentence and the value of baud rate.